A cross-sectional study of knowledge and stated practices regarding HIV among truck drivers in Basirhat health district, West Bengal - Halder, Tanudipta; Pal, Jayita; Debnath, Priya; Ghosh, Manoj (International Journal Of Community Medicine And Public Health, 2024)
Background: HIV is an important public health problem throughout the world as well as in India and truck drivers are a vulnerable population. A cross-sectional study was designed aiming to assess the knowledge and stated practices of truck drivers regarding HIV transmission, and prevention of its associated factors in Basirhat Health District, West Bengal. Methods: This study employed a rigorous cross-sectional design to assess the knowledge and practices of 111 truck drivers in Basirhat Health District, West Bengal, regarding HIV. Participants were selected using simple random sampling from parking zones and Dhaba. Data were collected through face-to-face interviews using a structured questionnaire. Results: The study uncovered intriguing insights into the knowledge and practices of truck drivers regarding HIV/AIDS. While the majority of participants had heard about HIV/AIDS, around half of the participants demonstrated good knowledge of HIV/AIDS. Surprisingly, misconceptions prevailed, including the belief that mosquitoes can transmit HIV. Participants displayed limited knowledge of AIDS symptoms and preventive measures, with uncertainty surrounding free HIV testing locations and free treatment availability. Alarmingly, a staggering 88.29% of truck drivers had never sought HIV testing, citing various reasons. Conclusions: The study underscores the necessity of targeted interventions to address knowledge gaps and promote safe sexual practices among truck drivers in the Basirhat Health District. Health workers and media campaigns can play a pivotal role in increasing awareness and prevention of HIV/AIDS among this population.